2015
DOI: 10.1093/gerona/glv126
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed Predicts Incident Disability: A Pooled Analysis

Abstract: In older adults, gait speed predicts 3 year incidence of bathing or dressing dependence, mobility difficulty, and a composite outcome of disability and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
238
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 344 publications
(267 citation statements)
references
References 40 publications
13
238
2
14
Order By: Relevance
“…Thus, it is possible that there was a lack of power to detect a difference in our results among males. Second, previous literature has found that slower gait speed is associated with an increased risk of dressing dependence among women, but not in men 45 , indicating that the low physical performance and muscle strength have more deleterious effects in women than in men. In agreement with our findings, sarcopenic obesity was associated with the onset of depression in women and not in men in a large study involving older English people.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, it is possible that there was a lack of power to detect a difference in our results among males. Second, previous literature has found that slower gait speed is associated with an increased risk of dressing dependence among women, but not in men 45 , indicating that the low physical performance and muscle strength have more deleterious effects in women than in men. In agreement with our findings, sarcopenic obesity was associated with the onset of depression in women and not in men in a large study involving older English people.…”
Section: Discussionmentioning
confidence: 93%
“…Walking speed is considered the most reliable physical performance measure for predicting the onset of disability in community‐dwelling older adults,34 especially for very old persons (e.g. aged 75 years and older) 2.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In the context of PST, someone who walks slowly may have an underlying disability that inhibits their ability to fully engage in interactive problem-solving exercises. Gait speed is also correlated with physical and cognitive health; slowed gait predicts frailty, disability, falls, functional dependence, [24][25][26] psychomotor speed slowing, and poor executive dysfunction, 27 the latter two which are only minimally tested in the Repeatable Battery for the Assessment of Neuropsychological Status.…”
Section: Discussionmentioning
confidence: 99%